Optimizing Indonesian Language in Online News for National Identity: Enhancing Engaging Narratives and Competence - Eka Putra; Muhammad Fithra; Wen Jia; Nuradlin Syafini; Khusnul Hanafi; Harun Mukhtar; W. M. Azim (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Sumatera Barat, 2024)
This article delves into the investigation of journalists' competence in Riau Province, specifically examining their proficiency in writing news for online media. Adopting a pluralistic approach to languages, the study places a strong emphasis on understanding the interconnections between language and various facets of human life, such as culture, cognition, and society. The research extensively explores the entire journalistic process, encompassing information gathering and news composition, with a specific focus on the significance of proficient Indonesian usage. Proficient language use is deemed crucial for effectively conveying information and upholding journalistic standards. Employing a qualitative approach, the study conducts in-depth interviews with six experienced journalists from diverse online media outlets in Riau. Findings underscore the existing usage of Indonesian by journalists in the region but reveal opportunities for further optimization. Aligning Indonesian with journalistic concepts is identified as crucial for creating impactful and enjoyable news content. The research highlights a competence gap in news writing using Indonesian, underscoring the imperative need for enhancement. Despite this, regional languages are recognized for their supportive role in aiding journalists during fieldwork, presenting both challenges and opportunities that call for a nuanced approach. The limited optimization of Indonesian language use in news writing prompts a call for additional training and development to refine journalists' competencies. While challenges exist, strategically incorporating regional languages is recognized as a potential benefit. This research provides valuable insights, serving as a foundation for enhancing the Indonesian language skills of online media journalists in Riau, ultimately contributing to the overall quality and impact of news dissemination in the region.